UPAYA PEMBERDAYAAN MENTALITAS MELALUI KEGIATAN BACA TULIS PADA ANAK PANTI ASUHAN DEWI KARUNIA - Haratua Aritonang; Hairani Siregar (JOURNAL SAINS STUDENT RESEARCH, 2024)
This journal explains several efforts to empower the mentality of children living in the Dewi Karunia orphanage. This is an effort by social welfare students at the University of North Sumatra to provide a real presence in society and apply the knowledge learned from the lecture period they have undergone. In the current era, the amount of discrimination against children in orphanages has become a big problem that cannot be ignored. Children who live in orphanages every day must receive good social treatment. The treatment in question is educational facilities, learning facilities, a healthy environment and most importantly having a good mentality like children in general. There are social issues that are clearly heard, namely that children living in orphanages have abilities that are below average compared to children in general. This problem is an imbalance that should not occur. Orphanage children must have a high spirit and mentality. With this, they will be able to compete with children in general. Their limitations in terms of family can be the main factor in their lack of encouragement in adapting to the environment and learning. However, all of this can be overcome by implementing reading and writing. Over time, the implementation of the reading and writing system has had a positive impact on the children at the Dewi Karunia orphanage. They started to open up when invited to discuss. Many of them are serious about learning. Limited encouragement in the family means that orphanage children have to learn independently. They must get used to living independently. There are still many of them who are still not fluent in reading and writing. Many of the children in the orphanage are still not fluent in arithmetic. Efforts to empower mentality through literacy programs really help orphanage children to continue to develop. Not only that, they can also easily understand every lesson they take part in at school. At their current age, character formation can start early. This aims to ensure that every child in the Dewi Grace orphanage can grow both mentally and intellectually. I will implement this empowerment effort within a period of four months. Seeing all this requires patience in giving directions. Foresight, perseverance and good preparation can help efforts to empower children through the application of reading and writing to children at the Dewi Karunia orphanage.